Comparative analysis of isoform-specific and non-selective histone deacetylase inhibitors in attenuating the intestinal damage after hemorrhagic shock - Bhatti, Umar F (Trauma Surg Acute Care Open, 2019)
BACKGROUND: Isoform-specific histone deacetylase inhibitors (HDACIs) MC1568 and ACY1083 are comparable to the non-selective HDACI valproic acid (VPA) in improving survival in rodents undergoing lethal hemorrhage. However, the organ-specific properties of isoform-specific HDACIs have not been fully evaluated. Also, whether they can act synergistically is not known. We hypothesized that isoform-specific HDACIs are superior to VPA in attenuating intestinal injury and act synergistically when coadministered. METHODS: Sprague Dawley rats were hemorrhaged (40% of total blood volume) and randomized to receive (n=4 per group) (1) MC1568 (5 mg/kg), (2) ACY1083 (30 mg/kg), (3) MC1568+ACY1083 (combination: 5 mg/kg + 30 mg/kg, respectively), (4) VPA (250 mg/kg), or (5) normal saline (NS; vehicle; 250 μL). Animals were observed for 3 hours, after which blood samples were collected and samples of the ileum were harvested. Expression of interleukin 1 beta (IL-1β), tumor necrosis factor alpha (TNF-α), and cytokine-induced neutrophil chemoattractant 1 (CINC-1) was assessed in the tissues using enzyme-linked immunosorbent assay. Intestinal cleaved caspase 3 (c-caspase 3) levels were assessed as a marker of apoptosis, and histologic sections of the ileum were examined for signs of bowel injury. Levels of IL-1β and TNF-α were also measured in the serum as global markers of inflammation. RESULTS: Treatments with MC1568, ACY1083, MC1568+ACY1083, and VPA were associated with decreased IL-1β levels in the intestine and serum compared with NS. IL-1β and TNF-α levels were significantly lower in the ACY1083 group compared with the VPA group. CINC-1 levels were significantly lower in the isoform-specific HDACI groups compared with the NS; however, no significant differences were seen with VPA. All treatment groups had a lower expression of intestinal c-caspase 3 compared with NS. Furthermore, MC1568 and ACY1083 groups had lower apoptosis compared with the VPA group. Bowel injury scores were significantly lower in the isoform-specific HDACI groups compared with the NS group; however, the attenuation in the VPA-treated animals did not reach statistical significance. DISCUSSION: Isoform-specific HDACIs provide superior intestinal protection compared with VPA in a rodent model of hemorrhagic shock. LEVEL OF EVIDENCE: Preclinical study.